The Exile of Kiai Modjo in Tondano and His Role in the Formation of the Jaton Community in Minahasa 1825-1849 - Kembuan, Roger Allan Christian; Amri, Khaerul; Wallidaeny, Alwin Firdaus (Kawanua International Journal of Multicultural Studies, 2025)
Previous studies on the Java War have focused primarily on military conflict and colonial punishment, paying limited attention to the post-war lives of Muslim exiles and the mechanisms of coexistence that emerged in exile destinations such as Minahasa. This article addresses that gap by examining how the exile of Kiai Modjo and his followers after the Java War (1825–1830) contributed to the formation of a Muslim minority community within a predominantly Christian social space. This study asks how did colonial exile function as a mechanism of governance, and through what social and institutional practices was coexistence negotiated in Minahasa? Drawing on colonial archival records, an Arabic Pegon manuscript, and oral traditions from Kampung Jawa Tondano, the article analyzes exile as both a strategy of colonial containment and an unintended process of minority-making. The findings argue that coexistence did not take the form of abstract pluralism, but emerged as a negotiated social practice shaped by settlement-making, religious institutionalization, economic activity, and inter-communal relations, including marriage and conversion. By reframing exile as a generative historical process, this article contributes to discussions on Muslim minorities, interfaith encounters, and identity negotiation in colonial Indonesia.